Microvascular Skin Manifestations Caused by COVID-19 - Gawaz, Andrea; Guenova, Emmanuella (Hämostaseologie, 2021)
Hypercoagulability and vascular injury, which characterize morbidity in COVID-19 disease, are frequently observed in the skin. Several pathomechanisms, such as inflammation caused by angiotensin-converting enzyme 2–mediated uptake into endothelial cells or SARS-CoV-2-initiated host immune responses, contribute to microthrombus formation and the appearance of vascular skin lesions. Besides pathophysiologic mechanisms observed in the skin, this review describes the clinical appearance of cutaneous vascular lesions and their association with COVID-19 disease, including acro-ischemia, reticular lesions, and cutaneous small vessel vasculitis. Clinicians need to be aware that skin manifestations may be the only symptom in SARS-CoV-2 infection, and that inflammatory and thrombotic SARS-CoV-2-driven processes observed in multiple organs and tissues appear identically in the skin as well.
Keywords: COVID-19; skin manifestation; microvascular